THE INFLUENCE OF LIFESTYLE ON THE PURCHASE DECISION OF APPLE SMARTPHONE PRODUCTS ON STUDENTS OF THE FACULTY OF SOCIAL SCIENCES AND POLITICS MALIKUSSALEH UNIVERSITY - Susilawati; Nursanjaya; Sufi; Lisa Iryani; Nanda Ameliany (RADJA PUBLIKA, 2025)
This article discusses the influence of lifestyle on the decision to purchase Apple smartphone products among students of FISIPOL, Malikussaleh University. This study aims to determine the influence of lifestyle on the decision to purchase Apple smartphone products among students of FISIPOL, Malikussaleh University. The type of research used in this study is quantitative. The population in this study were all students of FISIPOL, Malikussaleh University. Sampling used 100 respondents using the Slovin formula. The data collection technique used a Likert scale. The data processing and analysis techniques in this study used SPSS 26. The first stage in this study was the instrument test, namely the validity test and reliability test. Furthermore, data analysis techniques were carried out with the classical assumption test, simple linear regression test and hypothesis test. The results of this study indicate that: lifestyle (X) has a positive and significant effect on the decision to purchase Apple smartphone products among students of FISIPOL, Unimal with a t-count value of 11.391> t-table 1.985 and a sig value of 0.000 <0.05.